Communication in Personal Selling Activities of MSMEs Actors - Mutiah; Norhabiba, Fitri; Sukardani, Puspita Sari; Setiadi, Tatak (Proceeding of International Joint Conference on UNESA, 2024)
Seeing the condition of MSMEs with limited human resources in the use of media and technology, most MSME players mostly practice personal sales. Personal selling is an alternative because it is considered to be enough to reduce promotional costs. Personal selling is direct or face-to-face communication between sellers and potential customers to introduce a product to potential customers and form customer understanding of the product so that they will then try and become customers. MSMEs in Taman Sub-district of Sidoarjo is a group of MSMEs that has a large membership, with more than 20 active members who have production activities ranging from food and beverages, handicrafts and others. The activities of members of the human resource development of MSME actors are carried out at the secretariat which was donated by the head of Taman Sub-district for the activities of business actors. Usually the activities they carry out are about improving the skills to produce certain goods, training in proposing halal certificates, training from agencies and universities. The training provided is based on the needs of the MSME actors themselves, starting from packaging training, finding capital partners, product photos, product videos. MSME actors generallys have basic skills in production and promoting their products, but they still do it independently. Although efforts to partner with various parties are made to market MSME products, in the end, Taman sub-district MSME players prefer to market their products by personal selling. Personal selling activities are more efficient and effective, no need to depend on uncertain cooperation offers from their partners. Therefore, this research will look at how communication in personal selling activities by MSME players in Sidoarjo with a qualitative approach and phenomenological method